2008
DOI: 10.18814/epiiugs/2008/v31i2/009
|View full text |Cite
|
Sign up to set email alerts
|

The Quaternary: its character and definition

Abstract: The Quaternary is characterised by the development of widespread glaciations in mid-northern latitudes. As a chronostratigraphic term it has attracted vigorous debate. The Quaternary, as accepted by the International Union for Quaternary Research and proposed by the International Commission on Stratigraphy, begins at 2.6 Ma within a 2.8-2.4 Ma interval of profound change in Earth's climate system. The base of the Gelasian Stage at 2.588 Ma offers an existing global stratotype section and point to define the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 35 publications
1
30
0
5
Order By: Relevance
“…A major cooling event is observed at around 3.30 Ma in the mid‐Pliocene marine isotope stage (MIS) M2 [ Prell , 1984; Keigwin , 1987; Shackleton et al , 1995; Jansen et al , 2000; Lisiecki and Raymo , 2005; Tiedemann et al , 2006; Head et al , 2008]. Also known as the Mammoth cooling event after the Mammoth Subchron in which it occurs, MIS M2 may represent a failed attempt of the climate system to reach a full glacial state [ Haug and Tiedemann , 1998].…”
Section: Introductionmentioning
confidence: 99%
“…A major cooling event is observed at around 3.30 Ma in the mid‐Pliocene marine isotope stage (MIS) M2 [ Prell , 1984; Keigwin , 1987; Shackleton et al , 1995; Jansen et al , 2000; Lisiecki and Raymo , 2005; Tiedemann et al , 2006; Head et al , 2008]. Also known as the Mammoth cooling event after the Mammoth Subchron in which it occurs, MIS M2 may represent a failed attempt of the climate system to reach a full glacial state [ Haug and Tiedemann , 1998].…”
Section: Introductionmentioning
confidence: 99%
“…1) in Calabria, southern Italy, which formerly served as the GSSP of the Plio‐Pleistocene boundary (Aguirre and Pasini, 1985) and remains available as the GSSP for the Calabrian Stage (Gibbard et al ., 2010; Gibbard and Head, 2010). We note that the Pleistocene and Quaternary are now both defined by the Gelasian Stage GSSP at Monte San Nicola in Sicily, their bases dated at 2.58 Ma (Head et al ., 2008a; Gibbard and Head, 2009a,b, 2010). Two candidate GSSPs for the Middle Pleistocene Series (Head et al ., 2008b), the Valle di Manche section (Capraro et al ., 2005) and Montalbano Jonico section (Brilli et al ., 2000; Stefanelli et al ., 2005; Ciaranfi and D'Alessandro, 2005), are also located in Italy (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, Carri on et al (2009) reported on the palynological sterility of the coprolites of P. brevirostris preserved in micritic limestone at Venta Micena. As a result, ice-rafted debris records of the Nordic Seas and North Atlantic show stepwise increase between 3.5 and 2.4 Ma, which evidences the presence of large ice sheets in the northern hemisphere (Head et al, 2008). Gibert et al (2015) indicate an EarlyeMiddle Pleistocene climatic transition between 1.2 and 0.7 Ma, "when the climatic system underwent major changes, with the establishment of large ice sheets in the northern hemisphere."…”
Section: Paleoenvironmental and Paleoecological Interpretationmentioning
confidence: 99%